Reconstruction of Civics Learning Based on the Green Constitution to Improve Ecological Citizenship of Vocational High School Students: A Mixed Methods Approach - Sukmawati Sukmawati; Jamaludin; Shofia Nurun Alanur; Windy Makmur; Alif Akbar; Muhammad Nur Ali; Agustan Syam (Lembaga Bale Literasi, 2026)
Environmental degradation and socio-ecological crises in Indonesia underscore the urgent need to integrate constitutional environmental values into educational practices. However, Civics Education (PPKn) remains largely cognitive-oriented and has not effectively cultivated students’ ecological citizenship. This study examines the effectiveness and underlying mechanisms of reconstructing Civics learning based on the Green Constitution, integrated with a Deep Learning approach, to enhance students’ ecological citizenship. A mixed methods approach with a sequential explanatory design was employed, involving 100 tenth-grade vocational high school students in Sigi Regency. Quantitative data were collected using pre-test and post-test instruments and analyzed through descriptive statistics and N-Gain to measure learning improvement. Qualitative data, including classroom observations, interviews, and student reflections, were used to enrich and validate the quantitative findings. The results indicate significant improvements across all dimensions of ecological citizenship. These findings demonstrate that integrating Green Constitution principles with a Deep Learning approach effectively strengthens both the cognitive and affective dimensions of ecological citizenship. Nevertheless, while awareness and responsibility improved substantially, translating these gains into consistent active participation remains a challenge. Therefore, further pedagogical efforts are required to bridge the gap between ecological awareness and sustained civic engagement in real-world contexts.